Alcohol mixed energy drink use as a risk factor for experiencing and perpetrating bar aggression - Quigley, Brian M; Miller, Kathleen E; Eliseo-Arras, Rebecca K; Ball, Natalie J (Psychology of addictive behaviors, 2019)
Despite the recent, widespread trend of consuming alcohol mixed with energy drinks (AmEDs) in commercial bar settings, few studies have examined whether this practice exacerbates the risk of experiencing aggression in bars and licensed establishments. Past studies have been limited to between-subjects comparison analyses that are at risk for bias due to selection effects. The present analysis examines whether a sample of individuals who regularly use AmEDs are at elevated risk for experiencing or perpetrating physical aggression in bars when drinking AmEDs versus when they are drinking noncaffeinated alcohol (NCA) use alone. This within-subject analysis controls for any individual differences that may be related to both AmED use and the tendency to engage in aggressive behavior. An online survey was completed by 175 young adults (78 male) who were frequent bar patrons, used AmEDs regularly, and had experienced at least one recent bar conflict incident. Although NCA use was more common than was AmED use, AmED-involved bar aggression was more frequently reported than was aggression that coincided with NCA use only. Additionally, victimization and perpetration of aggression in bar environments were both more common when AmEDs were used than when only NCA was used. Frequency of going to bars was predictive of rates of experiencing bar aggression only when drinking NCA but not when drinking AmEDs. Results suggest that AmED use introduces a unique risk factor into the bar environment that must be considered in future research and in subsequent interventions meant to reduce the incidence of bar aggression. (PsycINFO Database Record (c) 2019 APA, all rights reserved).